Pengembangan Bisnis Toko Wingko “Kelapa Muda” - Kurniawan, Ricky Wijaya; Munir, Ningky Sasanti (Journal of Emerging Business Management and Entrepreneurship Studies, 2021)
Development of a business model that provides analysis of weaknesses and takes advantage of opportunities, as well as in-depth information that is evaluated and used for competition in modern markets and the impact of Covid-19. Through the Business Model Canvas (BMC) which maps strategies based on an analysis of strengths, weaknesses, threats and opportunities. The results of the analysis will be redeveloped through the Blue Ocean Strategy (BOS) with the ERRC Grid approach from eliminating, increasing, reducing, and creating. Guided by the "create" element to provide the development of business value from factors that have never existed before and will be formed into the "Kelapa Muda" Wingko Shop Business Model Canvas. Based on the recommended steps for active social media marketing and in-site sales, distributors, retailers, and online e-commerce, it is targeted to provide revenue value to grow by 3 (three) times the value of gross income in 2019.